Assessing the new ICD-MM classification for assigning the cause of maternal mortality at a tertiary centre in Western India: a retrospective study - Sheth, Tosha M.; Vaishnav, Palak P.; Maitra, Nandita K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The World Health Organisation (WHO) in 2012 introduced the 10th revision of International Classification of Disease (ICD 10) to deaths in pregnancy, labour and puerperium (ICD-MM) for consistent collection, analysis and interpretation of information on maternal deaths. The proper use of this classification requires training to avoid heterogeneity and error in the classification of maternal deaths. Methods: We analysed the Maternal Death Review (MDR) forms of 295 deaths over a period of 5 years (January 2014 to December 2018 inclusive) occurring at a tertiary health centre in Western India. The ICD-MM classification was used to reassign the cause of death. Results: There were 295 deaths in women during pregnancy, childbirth and puerperium during the 5 year period. Of these there were 294 maternal deaths and one coincidental death. There were 173 deaths of the direct type (58.84%), 105 deaths of the indirect type (35.71%) and 16 deaths (5.44%) of the unspecified type. Obstetric haemorrhage was the highest contributor to direct deaths (23.8%) and anaemia contributed to the maximum deaths from indirect causes (13.6%) followed by liver diseases in pregnancy (10.54%).Unanticipated complications of management accounted for 2% of the total deaths. There was considerable inaccuracy in assigning cause of death by consultants who were untrained in the use of the ICD-MM classification. Conclusions: ICD-MM classification promotes an accurate assignment of the cause of death. Training of healthcare providers performing maternal death reviews in the use of this classification is essential to identify accurate underlying cause of death and contributory conditions.